Differential expression of APO-1 on human thymocytes: implications for negative selection? - Debatin, Klaus-Michael; Süss, Dorothee; Krammer, Peter H. (European journal of immunology, 1994)
Negative selection during T cell ontogeny involves selective induction of apoptosis in thymocytes. In peripheral lymphoid cells, apoptosis may be mediated via the APO-1 pathway. Here we report that APO-1 is constitutively expressed on the vast majority of human thymocytes but down-regulated at a mature stage of thymocyte development (TCRhi). This stage of development is characterized by CD28hi, CD44hi, CD69hi and up-regulation of Bcl-2 protein. We define a new thymocyte subpopulation that expresses high levels of APO-1 and intermediate levels of T cell receptor α/β (TCRim/APO-1hi). The TCRim/APO-1hi population contains a large fraction of dead cells, suggesting that the APO-1 pathway may be involved in negative selection of at least a fraction of thymocytes after intrathymic activation.
Elektronische Reproduktion der Druck-Ausgabe 23. November 2005
Gesehen am 24.09.2024